2001
DOI: 10.1053/jhep.2001.20899
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of clevudine [?-FMAU, (1-(2-fluoro-5-methyl-β, ?-arabinofuranosyl) uracil)] against woodchuck hepatitis virus replication and gene expression in chronically infected woodchucks (Marmota monax)

Abstract: L-FMAU has markedly less toxicity than its D-enantiomer, D-FMAU, and L-FMAU does not induce an increase in lactic acid production in the human hepatoblastoma cell line, HepG2, as observed following exposure to D-FMAU and the related nucleoside analogue, D-FIAU (fialuridine). [1][2][3][5][6][7][8][11][12][13][14][15] Fialuridine demonstrated potent anti-HBV activity in clinical trials for chronic HBV infection, but also induced severe delayed toxicity associated with lactic acidosis and hepatic failure that res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
125
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 36 publications
8
125
1
Order By: Relevance
“…11 In the ongoing trials, we can now use the more recently developed real-time PCR assays (HBV Beacom assay and COBAS TaqMan HBV), which have a dynamic range of 1.0ϫ10 2 to 1.0ϫ10 9 /mL. 12,13 As shown previously in animal models 8 and by a phase I/II short-term clinical trial, 9 clevudine has the unique property of delayed time to viral rebound after treatment. The mechanisms of delayed viral recrudescence observed for 24 weeks after dosing remain to be elucidated.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…11 In the ongoing trials, we can now use the more recently developed real-time PCR assays (HBV Beacom assay and COBAS TaqMan HBV), which have a dynamic range of 1.0ϫ10 2 to 1.0ϫ10 9 /mL. 12,13 As shown previously in animal models 8 and by a phase I/II short-term clinical trial, 9 clevudine has the unique property of delayed time to viral rebound after treatment. The mechanisms of delayed viral recrudescence observed for 24 weeks after dosing remain to be elucidated.…”
Section: Discussionmentioning
confidence: 91%
“…6,7 In woodchucks infected with woodchuck hepatitis virus (WHV), clevudine led to a decrease in the plasma WHV DNA of up to a thousand-fold. 8 In addition, in a phase I/II clinical study, clevudine at once daily doses between 10 and 200 mg for 28 days was well tolerated and produced significant antiviral activity. Moreover, one particularly beneficial effect of clevudine was that viral suppression was maintained for as long as 24 weeks after discontinuation of treatment.…”
Section: Nfection With Hepatitis B Virus (Hbv) Is Commonmentioning
confidence: 99%
“…In chronically infected ducks treated with hepatocytotoxic reverse transcriptase inhibitors (24), in WHV-infected woodchucks treated with inhibitors of viral DNA replication (3,25), and in acutely WHV-infected woodchucks undergoing viral clearance (4, 7), there is strong evidence that cccDNA elimination depends on the death and turnover of infected hepatocytes. In other studies performed in HBV transgenic mice (9,15,26) and HBV-infected chimpanzees (10,11), it has been shown that viral replication is strongly and rapidly inhibited noncytopathically by the antiviral effects of IFN-␣͞␤ and IFN-␥, which eliminate the replicative DNA precursors of cccDNA from the cell (13).…”
Section: Discussionmentioning
confidence: 99%
“…focused primarily on a strategy of inhibiting viral DNA synthesis through the use of nucleoside analogs that are highly specific for the viral DNA polymerase (1)(2)(3)(4)(5)(6)(7)(8)(9). Treatment of patients with such inhibitors can be remarkably effective in reducing viremias to very low levels (2,3).…”
Section: Hemotherapy Of Hepatitis B Virus (Hbv) Infections Hasmentioning
confidence: 99%